2007
DOI: 10.1002/itdj.20067
|View full text |Cite
|
Sign up to set email alerts
|

Open access towards bridging the digital divide–policies and strategies for developing countries

Abstract: There is a consensus that Information and Communication Technologies (ICTs) hold great promise for development by connecting people to more accurate and up-to-date sources of information and knowledge. However, the evidence so far shows that the benefits accrued from the utilization of ICTs have been inequitably distributed with most developing countries (particularly Africa) facing the prospect of being marginalized. Inequality of access to information and technological advantages among scientists becomes a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Similarly, prior research, both within and outside developing countries, on the digital divide has focused primarily on illustrating specific technology initiatives and illuminating their success or failure (Heeks, 2002; Keniston, 2002; Keniston & Kumar, 2004; Ahmed, 2007) or examining the demographic characteristics of privileged and underprivileged classes (e.g. Lenhart, 2002; Hsieh et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, prior research, both within and outside developing countries, on the digital divide has focused primarily on illustrating specific technology initiatives and illuminating their success or failure (Heeks, 2002; Keniston, 2002; Keniston & Kumar, 2004; Ahmed, 2007) or examining the demographic characteristics of privileged and underprivileged classes (e.g. Lenhart, 2002; Hsieh et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many analyses and critiques have suggested that Open Access publishing is beneficial to African research production capabilities, scholars' reputations, and their institutions. Ahmed (2007) emphatically states that:…”
Section: Defining Parametersmentioning
confidence: 99%
“…The digital divide is a complex, and dynamic problem which has political, cultural, and ethical dimensions (Ahmed, 2007). According to Lei, Gibbs, Chang, and Lee (2008), there are two main different thoughts about how to deal with the digital divide.…”
Section: Acılarmentioning
confidence: 99%